1992
DOI: 10.1016/0014-5793(92)81529-u
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and metabolism of fluorescent ceramide analogs by rat oligodendrocytes in culture

Abstract: We studied tbc metabolism of sphingolipids by oligodendrocytes derived from rat spinal cord by providing lipid vesicles with cithcr N-lissamina rhodaminyl-cerumidc (LRh-Cer) or N-(7-nitrobcnz-2-oxo-I,3-diazol-4-yl)-ccramide (NBD-Cer) to the cells cultured in a chemically-defined mcdium. With both probes the major fluorescent product turned out to be sphingamyelin (SM). Most of LRh-SM WPS not cell-associated but recovered from lhe culture medium, probably due to back-exchange to the lipid vesicles. The accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Thereafter, products are formed at a higher rate and after 24 h of labelling, the cellassociated fluorescence is approx. 8 nmol/106 cells, of which maximally 1 nmol cells can be attributed to C~2-LRh-metabolites [15]. Therefore, we feel confident that the intracellular CI2-LRhCer concentration is not limiting C~2-LRh-SM synthesis.…”
Section: Purification Of Myelin and Assays For Sphingolipid Synthesizingmentioning
confidence: 89%
See 4 more Smart Citations
“…Thereafter, products are formed at a higher rate and after 24 h of labelling, the cellassociated fluorescence is approx. 8 nmol/106 cells, of which maximally 1 nmol cells can be attributed to C~2-LRh-metabolites [15]. Therefore, we feel confident that the intracellular CI2-LRhCer concentration is not limiting C~2-LRh-SM synthesis.…”
Section: Purification Of Myelin and Assays For Sphingolipid Synthesizingmentioning
confidence: 89%
“…This could result from: (i) a lack of substrate(s); or (ii) limited access of the residual fluorescent ceramide to SM synthase. Option (i) is unlikely, because we have demonstrated previously that only a small fraction of the cellassociated C~2-LRh-Cer is metabolized [15] and the intracellular level of CI2-LRh-Cer decreased but slightly (<20%) during the chase period (results not shown). Moreover, inspection by confocal scanning laser microscopy showed that the perinuclear region where the Golgi apparatus is situated was labelled intensely already after 3 h of incubation with C~2-LRh-Cer SUV (cf.…”
Section: Purification Of Myelin and Assays For Sphingolipid Synthesizingmentioning
confidence: 94%
See 3 more Smart Citations